KESALAHAN BAHASA DALAM PENULISAN PELAJAR FAKULTI BAHASA DAN KOMUNIKASI DI UNIVERSITI MALAYSIA SARAWAK - Ain Nur Atika, Agus (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Language errors among students occur due to linguistic and non linguistic factors. The purpose of this study is to identify the language mistakes and the consequences of language errors in student writing. The data was collected from 100 students in Year 2 and Year 3 Faculty of Language and Communication at Universiti Malaysia Sarawak. This study was conducted using existing text analysis methods and distribution of survey forms. The findings indicate that the errors in student’s writing can be categorized into the use of derivative errors which include the frequency of misuse of prefixes of 127 errors, the circumfixes of 116 errors and infixes of 73 errors. There are also errors that occur in the use of the word joint names such as from, to, in, on, and to which have frequencies of 105, 99, 85, 54, 42 and 21 respectively. In addition, the reasons for language mistakes in student writing were also identified through the distribution of 100 survey forms to Faculty of Language and Communication at Universiti Malaysia Sarawak.